Weather Information for Garden City, 2016 - J. Elliott (Kansas Agricultural Experiment Station Research Reports, 2017)
Precipitation for 2016 totaled 17.73 in. This was 1.51 in. below the 30-year average of 19.24 in. and followed two years of above normal moisture. April and July 2016 had considerably above average precipitation, causing good summer crop growing conditions. Rainfall diminished after July to 37% of the 30-year-average, resulting in dry conditions for fall wheat planting. Hail was not observed in 2016. Blowing dust was noted on two days in March. The largest daily rainfall events were 1.72 in. on April 16, and 1.68 in. on July 2.
Keywords: weather; Garden City weather; 2016 weather